1981
DOI: 10.1021/ja00409a030
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-induced oxidations of aromatic substrates: catalytic conversion of catechols to o-benzoquinones. Copper phenoxides as intermediates in the oxidation of phenol, and a single-step conversion of phenol, ammonia, and oxygen into muconic acid mononitrile

Abstract: Cupric chloride or bis( 1 -phenyl-l,3,5-hexanetrionato)dicopper(II) complex in the presence of triethylamine or copper(I1) species produced by reaction of cuprous chloride with oxygen in an aprotic solvent in the absence of added base all catalyze conversion of 3,5-di-tert-butylcatechol and 4-tert-butylcatechol with oxygen to the corresponding 1,2-benzoquinones. It appears that the catalytic sequence involves (a) formation of the dicopper(I1) catecholate intermediate, (b) electron transfer from the aromatic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…3,2528 p -Quinones are formed from oxidation of t -butylhydroquinone, hydroquinone, naphthohydroquinone, and thymohydroquinone. 25,2932 Oxidation of catechols in natural products [caffeic acid, carnosic acid, catechin, ellagic acid, epigallocatechin (ECGC), hydroxychavicol, luteolin, procyanidin, quercetin, taxifolin, and urushiols] gives o -quinones with a variety of biological effects (Table 2).…”
Section: Mechanism Of Quinone Formationmentioning
confidence: 99%
“…3,2528 p -Quinones are formed from oxidation of t -butylhydroquinone, hydroquinone, naphthohydroquinone, and thymohydroquinone. 25,2932 Oxidation of catechols in natural products [caffeic acid, carnosic acid, catechin, ellagic acid, epigallocatechin (ECGC), hydroxychavicol, luteolin, procyanidin, quercetin, taxifolin, and urushiols] gives o -quinones with a variety of biological effects (Table 2).…”
Section: Mechanism Of Quinone Formationmentioning
confidence: 99%
“…53 In their study of the kinetics of the reaction of 3,5-DTBCH 2 with dioxygen catalyzed by bis(1-phenyl-1,3,5-hexanetrionato)dicopper(II) complex, the authors showed that the overall reaction is first order in the substrate 53 Furthermore, these authors 55 reported a stoichiometric oxidation of 3,5-DTBCH 2 in anaerobic conditions to the respective quinone by a number of mononuclear and dinuclear copper(II) complexes, which was consistent with the first step of the mechanism proposed by Demmin, Swerdloff and Rogić. 54 They also made an interesting observation that mononuclear planar copper(II) complexes could not be reduced by 3,5-DTBCH 2 and showed very little catecholase activity in comparison to the readily reducible complexes. Thus, the catalytic activity of the complexes appeared to correlate with their reduction potentials.…”
Section: Model Systems Of Catechol Oxidase: Historic Overviewmentioning
confidence: 99%
“…44,45 Alternatively, Rogićand co-workers have proposed a single electron transfer step in the aerobic oxidation of catechols using catalytic CuCl/pyridine. 46,47 Hydrogen atom abstraction has also been invoked as a pathway in the oxidation of alcohols by several copper complexes that model the enzyme galactose oxidase. 48,49 In the aerobic oxidation of the simple lignin model compounds, the copper catalytic system exhibits quite different selectivity from the vanadium one.…”
Section: Coppermentioning
confidence: 99%